Assessing long term backache after childbirth. Issue 6888 (15th May 1993) - Russell, R; Groves, P; Taub, N; O'Dowd, J; Reynolds, F
Abstract : OBJECTIVES--To investigate the factors associated with long term backache after childbirth, to assess all women reporting new onset long term backache, and to investigate any relation with pain relief in labour. DESIGN--Data collected from obstetric records and postal questionnaires or telephone interviews on morbidity after childbirth from all women delivering their first baby between March 1990 and February 1991, followed by analysis of data collected from outpatient consultations. SETTING--St Thomas's Hospital, London. SUBJECTS--Questionnaires were sent to 1615 women who had delivered their first baby in the defined period; 1015 either replied by post or were contacted by telephone. RESULTS--299 women (29.5% of responders) reported backache lasting more than six months and of these 156 (15.4%) said they had had no back problems previously. Those women who had received epidural analgesia in labour were significantly more likely to report new onset backache (17.8%; 95% confidence interval 14.8% to 20.8%) than those who did not (11.7%; 8.6% to 14.8%). Younger women, unmarried women, and those reporting other antenatal symptoms were significantly more likely to report new long term backache. The 156 women reporting new backache were asked to attend an outpatient clinic and 36 (23%) did so. The majority had a postural backache which was not severe. Psychological factors were present in 14 women. CONCLUSIONS--Though new long term backache is reported more commonly after epidural analgesia in labour, it tends to be postural and not severe. There were no differences in the nature of the backache between those who had or had not received epidural analgesia in labour.